Impaired Antibody-Dependent Cellular Cytotoxicity in a Spanish Cohort of Patients With COVID-19 Admitted to the ICU - Vigón, Lorena; García-Pérez, Javier; Rodríguez-Mora, Sara; Torres, Montserrat; Mateos, Elena; Castillo de la Osa, María; Cervero, Miguel; Malo De Molina, Rosa; Navarro, Cristina; Murciano-Antón, María Aránzazu; García-Gutiérrez, Valentín; Planelles, Vicente; et al. (Frontiers in Immunology, 2021)
SARS-CoV-2 infection causes COVID-19, ranging from mild to critical disease in symptomatic subjects. It is essential to better understand the immunologic responses occurring in patients with the most severe outcomes. In this study, parameters related to the humoral immune response elicited against SARS-CoV-2 were analysed in 61 patients with different presentations of COVID-19 who were recruited in Hospitals and Primary Healthcare Centres in Madrid, Spain, during the first pandemic peak between April and June 2020. Subjects were allocated as mild patients without hospitalization, severe patients hospitalized or critical patients requiring ICU assistance. Critical patients showed significantly enhanced levels of B cells with memory and plasmablast phenotypes, as well as higher levels of antibodies against SARS-CoV-2 with neutralization ability, which were particularly increased in male gender. Despite all this, antibody-dependent cell-mediated cytotoxicity was defective in these individuals. Besides, patients with critical COVID-19 also showed increased IgG levels against herpesvirus such as CMV, EBV, HSV-1 and VZV, as well as detectable CMV and EBV viremia in plasma. Altogether, these results suggest an enhanced but ineffectual immune response in patients with critical COVID-19 that allowed latent herpesvirus reactivation. These findings should be considered during the clinical management of these patients due to the potential contribution to the most severe disease during SARS-CoV-2 infection.